Evolution of Sleep: Phylogenetic and Functional Perspectives - McNamara, Patrick (Cambridge University Press, 2013)
Research during the past two decades has produced major advances in understanding sleep within particular species. Simultaneously, new analytical methods provide the tools to investigate questions concerning the evolution of distinctive sleep state characteristics and functions. This book synthesizes recent advances in our understanding of the evolutionary origins of sleep and its adaptive function, and it lays the groundwork for future evolutionary research by assessing sleep patterns in the major animal lineages.